Evidence for a composite anterior determinant in the hover fly Episyrphus balteatus (Syrphidae), a cyclorrhaphan fly with an anterodorsal serosa anlage - Lemke, Steffen; Schmidt-Ott, Urs (Development, 2009)
Most insect embryos develop from a monolayer of cells around the yolk, but only part of this blastoderm forms the embryonic rudiment. Another part forms extra-embryonic serosa. Size and position of the serosa anlage vary between species, and previous work raises the issue of whether such differences co-evolve with the mechanisms that establish anteroposterior (AP) polarity of the embryo. AP polarity of the Drosophila embryo depends on bicoid, which is necessary and sufficient to determine the anterior body plan. Orthologs of bicoid have been identified in various cyclorrhaphan flies and their occurrence seems to correlate with a mid-dorsal serosa or amnioserosa anlage. Here, we introduce with Episyrphus balteatus (Syrphidae) a cyclorrhaphan model for embryonic AP axis specification that features an anterodorsal serosa anlage. Current phylogenies place Episyrphus within the clade that uses bicoid mRNA as anterior determinant, but no bicoid-like sequence could be identified in this species. Using RNA interference (RNAi) and ectopic mRNA injection, we obtained evidence that pattern formation along the entire AP axis of the Episyrphus embryo relies heavily on the precise regulation of caudal, and that anterior pattern formation in particular depends on two localized factors rather than one. Early zygotic activation of orthodenticle is separated from anterior repression of caudal, two distinct functions which in Drosophila are performed jointly by bicoid, whereas hunchback appears to be regulated by both factors. Furthermore, we found that overexpression of orthodenticle is sufficient to confine the serosa anlage of Episyrphus to dorsal blastoderm. We discuss our findings in a phylogenetic context and propose that Episyrphus employs a primitive cyclorrhaphan mechanism of AP axis specification.